Adapting film parody for the sitcom format: Mel Brooks's When Things Were Rotten (1975) and The Nutt House (1989). (8th May 2012) - Symons, Alex
The landmark sitcom studies by Brett Mills, Janet Staiger and David Marc have previously identified a tendency in the 'mainstream' American sitcom towards standardized production values, predictable storylines and socially 'conservative' comedy. However, Mel Brooks's projects When Things Were Rotten (1975) and The Nutt House (1989) are from a different tradition. Following in the 'intermedial' approach employed by André Gaudreault, this article examines the way Brooks constructed these shows by adapting material from his own 'surreal' Hollywood parody films – in particular, Blazing Saddles (1974) and Young Frankenstein (1974). By adapting the conventions of film 'parody' to the sitcom format, Brooks's sitcoms – along with similar shows by others – were 'innovative' and untypical to the tradition. More importantly, these intermedial projects suggest that Hollywood film has made a so far neglected contribution to the historical development of the American sitcom that still continues today.